2014
DOI: 10.1093/ejcts/ezu287
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after different non-sternotomy approaches to left single-vessel revascularization: a comparative study with up to 10-year follow-up

Abstract: MIDCAB, EACAB and RADCAB are associated with similar long-term survival and incidence of major adverse cardiac events (MACEs) in single-vessel surgical revascularization. However, the endoscopic approach was found to be free from the disadvantages of longer operating duration observed in RADCAB or higher incidence of angina and shorter freedom from MACEs observed in both MIDCAB and RADCAB groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…One study provided separate data for both the TECAB offpump and robotic MIDCAB groups, and was included for analysis in both groups (10). Eighteen additional studies reported on a mixture of different surgical techniques (18,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53). A summary of the study selection process is presented in the PRISMA chart in Figure 1, and a summary of study characteristics is presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study provided separate data for both the TECAB offpump and robotic MIDCAB groups, and was included for analysis in both groups (10). Eighteen additional studies reported on a mixture of different surgical techniques (18,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53). A summary of the study selection process is presented in the PRISMA chart in Figure 1, and a summary of study characteristics is presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one studies were excluded from the final analysis due to a mixed dataset for different surgical techniques (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53) or use of cardiopulmonary bypass (36)(37)(38)(39)(40)(41), or use of an outdated robotic system other than the da Vinci system (18,34,35). Of the patients who were included for statistical analysis in the selected studies on off-pump TECAB, on-pump TECAB and robotic MIDCAB, the mean age ranged from 58 to 67, and 51-88% of patients were male.…”
Section: Resultsmentioning
confidence: 99%
“…In consequence, mastering the endoscopic LITA harvest ensures the avoidance of possible coronary steal syndrome [18,19]. Sabashnikov et al [20] reported results of a team experienced in performing minimally invasive surgical revascularization in its various dimensions. They concluded that the endoscopic approach (EACAB) for LITA harvest is free from the disadvantages of longer operation duration observed in robotically assisted direct coronary artery bypass grafting (RADCAB) or higher incidence of angina and shorter freedom from MACEs observed in both MIDCAB and RADCAB groups [20].…”
Section: Discussionmentioning
confidence: 99%
“…Sabashnikov et al [20] reported results of a team experienced in performing minimally invasive surgical revascularization in its various dimensions. They concluded that the endoscopic approach (EACAB) for LITA harvest is free from the disadvantages of longer operation duration observed in robotically assisted direct coronary artery bypass grafting (RADCAB) or higher incidence of angina and shorter freedom from MACEs observed in both MIDCAB and RADCAB groups [20]. This fact clearly demonstrates that both high quality anastomosis and perfect LITA harvest remain essential for satisfactory clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Among other data, the articles presented CABG results, including robotic acquisition of internal thoracic artery (ITA) [9] and internal mammary artery (IMA) grafts [10], and comparisons of short- and long-term outcomes for various techniques [11, 12]. Results pertaining to MVR procedures were described by Algarni et al [13], while Senay et al [14] assessed the feasibility of procedures in patients with severe rheumatic valve insufficiency.…”
Section: Analysis Of Scientific Reportsmentioning
confidence: 99%